Analysis of a Compact and Superdirective Metamaterial-Inspired Monopole Antenna - Saber Dakhli; Hatem Rmili; Kourosh Mahdjoubi; Jean-Marie Floc’h; Fethi Choubani (International Journal of Antennas and Propagation)
The directivity of a metamaterial-inspired compact (0.145λ0) monopole antenna was investigated. The proposed structure is composed of a split-ring resonator (SRR) parasitic element placed in the vicinity of a monopole antenna. Two configurations denoted by A1 and A2 were considered depending on the position of the slot in the SRR element. By analyzing simulated and measured results, the superdirectivity (7.5 dBi for A1 and 9 dBi for A2) of the structure was discussed. It is found that the monopole-SRR and/or ground plane-SRR coupling effects may be responsible for the superdirectivity of the structure.